DIGITAL LITERACY PRACTICES OF EFL SPECIAL SCHOOL TEACHER: ENGLISH FOR MENTALLY RETARDED STUDENTS - Gwi Widayani; Lestari Budianto (UICELL, 2021)
Mentally retarded students learn English with difficulties. The limitation is related to the mental problems as the main obstacle to learn English. The use of digital tools can be very beneficial in teaching and learning English for mentally retarded students. There were several types of research related to mentally retarded students but there was no research about the digital literacy practices of special school teachers in teaching English. This paper investigates the digital literacy practices of teachers in teaching English for mentally retarded students. The participants of this research were 15 special school teachers from three special schools around Jakarta, Tangerang and Kediri. The data of this research was gained through an open-ended questionnaire, semi-structured interviews, and online observation. The result showed that teachers in special schools were able to use some applications and digital tools in their teaching such as Ms Office, Video, Whatsapp, Google Form and Cap Cut. Their functional skills have been well-developed. Moreover, they could operate and use these digital tools for teaching and it was affected by teachers’ ages and work-period. In line with digital literacy practices, the findings showed that teachers have already used some digital tools in some ways based on Hague and Payton framework: teachers could create digital contents such as power point, video, voice recording and images (creativity), 86.7% of teachers have selected useful material by watching the downloaded video before giving them to the students (critical thinking and evaluation), 73.3% of teachers used digital tools to introduce their students to foreign cultures to raise their tolerance among citizens (cultural and social understanding), teachers used video to promote collaborative learning (collaboration), 53% of teachers found no difficulties to find and select information (finding and selecting information ability), 86.7% of teachers liked to review the information then shared them with others (effective communication) and 66.7% of teachers used trusted websites to download teaching materials (e-safety). On the other hand, the findings showed that special school teachers faced some challenges in using digital tools for teaching mentally retarded students such as difficulties in downloading teaching materials, lack of internet access, less-focused students, number of students in class, short teaching period and in availability of teacher’s guide. With these conditions, teachers were expected to upgrade themselves by being long-life learners and being open-minded for any updates. Moreover, this paper contributed to English language teaching literature especially for mentally retarded students. Keywords: Digital Literacy; Special School; ELT